Oscillations in "brain-body-mind"-A holistic view including the autonomous system - BAŞAR, EROL (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2008)
Studies related to brain oscillations pervade the neuroscience literature. Functional correlates of oscillations in the delta, theta, alpha, beta and gamma frequency windows are interpreted in several ways. However, only a small number of reports indicate the need for overall interpretations by integrating all type of results. The present essay emphasizes the importance of developing a common overview by considering sensory and cognitive inputs, in studies comparing healthy subjects with subjects with cognitive impairments. By doing this, the present report briefly outlines some general aspects and rules in the study of brain oscillations. The use in clinical studies of drugs mimicking neurotransmitters is also taken into consideration for a more complete analysis. A prominent extension to the study of functional correlates of brain functions is the new emerging results in oscillatory processes in the spinal cord and the autonomous system. By integrating oscillations in all EEG frequency windows, together with oscillations in the spinal cord and the autonomous system, a Gedanken-Model denoted as "globally coupled oscillators" of brain-body-mind incorporation is proposed in order to gain new insights in the dynamics of neural systems. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Brain oscillations; Brain-body-mind; Oscillations in autonomous system; Coupled oscillators; Alpha; beta; gamma; theta; sympathetic-nerve discharge; evoked-potentials; 10-hz rhythm; multisecond oscillations; reticular-formation; auditory pathway; dynamics; memory; synchronization; beyin salınımlar; beyin-beden-zihin; özerk sistemde salınımlar; birbirine osilatörler; alfa; beta; gama; teta; sempatik sinir deşarj; uyarılmış potansiyeller; 10-hz ritim; retiküler oluşumu; işitsel yolu; dinamik; bellek; senkronizasyon